THE IMPACT OF SOCIAL MEDIA ON TEENAGERS: EXPLORING THE ROLE OF AI IN MITIGATING RISKS AND ENHANCING BENEFITS - Rajnish Jain (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Social media has become a fundamental aspect of modern teenage life, shaping how young people communicate, learn, and develop their identities. While these platforms offer significant benefits such as enhanced connectivity, educational opportunities, and creative expression, these platforms also present considerable challenges including cyberbullying, mental health concerns, and privacy risks. This comprehensive article examines the psychological and social impacts of social media on teenagers while exploring how artificial intelligence technologies can help create safer digital environments. It investigates current platform demographics, usage patterns, and both the positive and negative effects of social media engagement. The article further delves into AI-driven solutions for content moderation, mental health monitoring, and personalized user experiences. By analyzing implementation challenges, ethical considerations, and future technological developments, it provides insights into creating more supportive and secure social media environments for teenage users while maintaining the benefits of digital connectivity.